PERANCANGAN INTEGRASI SISTEM SUPPLY CHAIN MANAGEMENT PRODUKSI DI PT PUSTAKA IMAM SYAFII - Nabil, Nabil; Noor, Muwasiq Mochamad (Bina Nusantara University, 2010)
The advancement of information technology is needed by every company. One for instance is the company of PT Pustaka Imam Asy-Syafi’i, in religious book production. In its production process, the system is still conventional; therefore there are troubles found especially in communication, recording, and scheduling. The purpose of this research is to analyse and design a production process system that create the latest that could help solving today’s production process problems. The research method that use dis data collecting method in doing quetionnaire analysis and analysis method by analysing needs and giving solution system, and then designing method application. The result concluded is the integrated production system that could increase production process work, which will be seen from value changing of a SWOT in the company. The conclusion could be seen from the second SWOT result which consists of increased performance in scheduling production process, increased performance in reporting production process, and increased communication effectivity per section.Keywords: production, SWOT, supply chain management